Roadmaps for tracking impacts of climate - smart investments: insights from African small and medium-sized agribusinesses. - Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report showcases an innovative approach we developed to empower agribusinesses in measuring and tracking their impacts on people and the environment, in a changing climate context. We summarize key elements and steps of the impact measurement process, which have been elaborated in more detail elsewhere (see https://aiccra.cgiar.org/)/. In the second part, we provide insights from collaborating with over fifty Africa-based agribusinesses between 2022 and 2024, who joined us on this journey of impact measurement. By distilling key elements of their diverse impact priorities, we aim to highlight the breadth of positive change that the agribusiness sector can drive across the continent, while also offering inspiration and practical guidance to those just beginning their own journey.Finally, we conclude by discussing critical learnings to strengthen the integration of impact measurement into agribusiness strategies, ensuring they contribute to more sustainable and resilient food systems.